Measuring changes in residential segregation in Port Elizabeth, South Africa, from 1996-2011 - Odayar, Luveshni (Rhodes University, Faculty of Science, Department of Geography, 2016)
Racial segregation and inequality were the prime objectives of the colonial and apartheid spatial planning policies that governed the spatial development of the South African urban landscape. Since South Africa's democratic transition after 1994, efforts have been made by government to facilitate racial integration and transform the apartheid urban fabric. Research into post-apartheid segregation is crucial to assess the success of governmental actions enacted thus far, while informing future spatial planning strategies. Most studies of these processes have relied solely on dichotomous indices to measure the extent of segregation between two groups. Few have utilized multi-group indices, which are more suited to investigating changes in multi-ethnic cases. Furthermore, the segregation indices used are typically aspatial. This study investigates the extent to which the segregationist legacy prevails in Port Elizabeth, a place widely considered to be the founding city of urban racial segregation. It also aims to investigate the impact of geographical scale on segregation. Theil's multi-group Entropy Index and Duncan and Duncan's Dissimilarity Index were derived from racial population data from the 1996, 2001 and 2011 National Censuses, and GIS was used to map changes in racial diversity both at tract level and across a range of geographical scales. To generate a more holistic understanding of the observed trends, statistical tests were performed to relate the observed patterns to socio-economic determinants, and feedback from the relevant government department was obtained. The results from the entropy indices reveal that segregation levels in Port Elizabeth have declined but still remain high: 84.6 % (1996), 79.2 % (2001) to 71.5 % (2011). This is a similar trend to those found in Cape Town and Johannesburg. The integration that did occur was characterized by one-way patterns of movement into former-White areas; this was predominantly confined to the Indian population, and to a lesser extent, the Coloured population. The vast majority of the African population remains confined to their former designated location areas. The White population remains the most segregated group, despite most of the racial integration occurring in former-White areas. Interview results and statistical tests revealed that persisting racial discrepancies in socio-economic factors (income, employment and education) can be considered major drivers influencing the observed trends in racial integration and persisting desegregation, as well as self-segregation.
Keywords: Uncatalogued